Effects of silicone and ascorbyl palmitate on the quality of palm olein used for frying of prawn crackers - Augustin, Mary Ann; Chua, Carlton J. J.; Heng, Lee Kheng (John Wiley & Sons, Ltd, 1987)
The effects of ascorbyl palmitate (AP) and silicone on the quality changes of refined, bleached and deodorised palm olein (RBD olein) during intermittent frying of prawn crackers for 4.5 h per day were evaluated. The percentage polar components, the C18:2/C16:0 fatty acid ratio, and the acid value of used frying oil without additives were comparable to those for oil containing 200 mg kg−1 AP. Oil with 2 mg kg−1 silicone as well as oil containing 200 mg kg−1 AP plus 2 mg kg−1 silicone that had been used for frying had lower percentage polar components, higher C18:2/C16:0 ratios and lower acid values than RBD olein without additive. The results showed that silicone had a protective effect on the oil but that the rate of deterioration of the oil in the presence of AP was comparable to that of oil without additive during frying of prawn crackers. The results also showed that the extent of oil oxidation in RBD olein subject to static heating at 180°C for 4.5 h per day for four consecutive days was comparable to that of RBD olein without additive that had been used for frying of prawn crackers.